Relationship between chronotropic incompetence and β-blockers based on changes in chronotropic response during cardiopulmonary exercise testing. (1st March 2015) - Takano, Nami; Takano, Haruhito; Fukuda, Taira; Kikuchi, Hironobu; Oguri, Gaku; Fukumura, Kazuya; Iwasawa, Kuniaki; Nakajima, Toshiaki
Abstract: Background: Chronotropic incompetence (CI), an attenuated heart rate (HR) response to exercise, is common in patients with cardiovascular disease. The aim of this study was to assess changes in the chronotropic response (CR) during cardiopulmonary exercise testing (CPET) in patients undergoing cardiac rehabilitation and investigate the effects of β-blockers. Methods: Patients undergoing cardiac rehabilitation performed CPET. Failure to achieve 80% of the age-predicted maximal HR (APMHR) defined CI. Values of the metabolic chronotropic relationship (MCR) were calculated from the ratio of the HR reserve to metabolic reserve at 4 stages, warm-up (MCR-Wu), anaerobic threshold (MCR-AT), respiratory compensation (MCR-Rc), and peak point (MCR-Pk), using the Wilkoff model. In patients who showed an increase in MCR at ≥ 3 of the 4 exercise stages, CR was considered to have improved. Results: Patients with high BNP levels (≥ 80 pg/ml) had a lower MCR at all stages compared with those with low BNP levels (< 80 pg/ml). Of the 80 patients, 47 showed an increase in both peak VO2 and AT, and of these 31 (66.0%) were taking β-blockers. Improvement in CR was observed in 30 of 47 patients with CI, and 70% of these were taking β-blockers. In patients not taking β-blockers, MCR-AT was lower than MCR-Rc, whereas in those taking β-blockers MCR-AT was higher than MCR-Rc. Conclusions: An attenuated HR response may occur during the early stages of exercise. The HR response according to the presence or absence of β-blockers is clearly identifiable by comparing MCR-AT and MCR-Rc using the Wilkoff model. Highlights: We have standardized definitions of CI objectively based on the Wilkoff model. An attenuated HR response may occur during the early stages of exercise. MCR values without β-blockers decreased from warm-up to AT and increased after AT. MCR values with β-blockers decreased from warm-up to Rc and increased after Rc. Cardiac rehabilitation increased peak VO2 with an improvement in HR response.